Modelling the relationship between intelligence, knowledge management and innovation among knowledge workers in Malaysia - Abd Karim, Zulkarnain; Noordin, Mohd Fauzan (IIUM Press, International Islamic University Malaysia, 2017)
This book examines one of the important aspects of the relationship between knowledge management and innovation - the influence of the people. From the literature review, it is discovered that most studies examined the relationship between knowledge management (KM) and innovation at an organizational or administrative level. This study took a different approach by researching the relationship between KM and innovation at an individual level. It aims to complement the understanding of the relationship between KM and innovation by examining the influence of individual human intelligence (i.e. Intellectual Quotient (IQ), Emotional Quotient (EQ), and Spiritual Quotient (SQ)) on their KM practices and innovation performance. To do that, seven hypotheses were formulated and tested to achieve the objectives.